2021
DOI: 10.1007/s11065-021-09527-y
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of the Effect of Antiretroviral Therapy on Neurocognitive Outcomes in Adults Living with HIV-1 in Low-and Middle-Income Countries

Abstract: HIV-associated neurocognitive impairment remains a challenge even in the era of antiretroviral therapy (ART). Over 90% of people living with HIV are in low-and middle-income countries. Hence, it is not surprising that such countries bear a considerable burden of comorbidities like HIV-associated neurocognitive impairment despite an overall increase in life expectancy. The literature suggests differences in patient characteristics, clinical profile, prevalent HIV subtypes, treatment choices, pharmacogenetics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 149 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, long-term exposure to ART medications can be associated with neurocognitive impairment [55,56]. The neurotoxic and neuropsychiatric impacts stemming from both the ART and the HIV infection itself necessitate a more comprehensive grasp of the pathological, pharmacological and behavioural mechanisms involved into the worsening of the cognitive function of PLWH [57][58][59][60].…”
Section: Association Of Art Self-efficacy With Depression Symptoms An...mentioning
confidence: 99%
“…On the other hand, long-term exposure to ART medications can be associated with neurocognitive impairment [55,56]. The neurotoxic and neuropsychiatric impacts stemming from both the ART and the HIV infection itself necessitate a more comprehensive grasp of the pathological, pharmacological and behavioural mechanisms involved into the worsening of the cognitive function of PLWH [57][58][59][60].…”
Section: Association Of Art Self-efficacy With Depression Symptoms An...mentioning
confidence: 99%
“…Several studies have been conducted to prevent or delay cognitive function decline, which found that HIV infection, comorbidities, non-adherence to antiretroviral therapy (ART), and mental health symptoms may be crucial risk factors for aggravating cognitive impairment in aging PLWH [4][5][6][7][8]. Among these factors, mental health symptoms are a modifiable risk factor for early intervention of HAND [9][10][11][12]. Furthermore, aging PLWH may suffer from mental health symptoms more than general aging people due to negative illness perception [13][14][15], which may further affect cognition-related behavior such as non-adherence to ART [16,17].…”
Section: Introductionmentioning
confidence: 99%